Demarcação da madeira juvenil e adulta de Corymbia citriodora - Palma, Hernando Alfonso Lara [UNESP]; Leonello, Elaine Cristina [UNESP]; Ballarin, Adriano Wagner [UNESP] (My University, 2010)
This paper had the objective of determining the transition regions between the juvenile and mature wood of Corymbia citriodora (Eucalyptus citriodora) of 29 years of age from the Experimental Station of Forest Science (EECFA-LCF/ESALQ-USP), located in Anhembi, in the State of São Paulo. The regions of juvenile and mature wood were characterized through anatomical studies - axial fiber length - following the recommendations of the International Association of Wood Anatomists (1989) using disks at the DBH of the trees. The measurements of fiber length were made in equipment for acquisition, diagnosis and image analysis. Five slices were made for every centimeter, in the radial direction and six fiber lengths per slice were measured, producing 30 measurements per sample region. In the total, 1740 lengths of fiber were measured in three disks that were studied. Results indicate a trend of accentuated and linear increase for the length of fibers, from the pith to 11 cm of radial of about 79%. Between 12 cm and 19 cm of the radius, fibers length remained almost constant, and from that point on, the fiber length tended to slightly increase to the bark. It can be concluded that for these trees, at this height of sampling, when the tree has 29 years of age, the extension of the juvenile wood goes up to 52% of its radius.

O presente trabalho foi realizado com o objetivo de determinar a região de transição entre a madeira juvenil e adulta de Corymbia citriodora (Eucalyptus citriodora) com 29 anos de idade, procedente da Estação Experimental de Ciências Florestais (EECF–LCF/ESALQ-USP), localizada em Anhembi, SP. Foram caracterizadas as regiões de madeira juvenil e adulta, por meio de estudos anatômicos - comprimento das fibras axiais -, seguindo as recomendações do International Association of Wood Anatomists (1989), utilizando-se discos ao DAP das árvores. As medições de comprimento das fibras foram realizadas em equipamento de aquisição, diagnóstico e análise de imagens. Foram montadas cinco lâminas, a cada centímetro, na direção radial e mensurados seis comprimentos de fibras por lâmina, perfazendo um total de 30 medições por região amostrada. No total, foram mensurados 1.740 comprimentos de fibras em três discos estudados. Os resultados indicam tendência de aumento acentuado e linear no comprimento das fibras, da ordem de 79%, da medula até 11 cm de raio. Entre 12 cm e 19 cm do raio, o comprimento se mantém quase constante e, a partir desse ponto, o comprimento das fibras aumenta levemente até a casca. Dessa forma, pode-se concluir que, para essa espécie e altura de amostragem quando a árvore tem 29 anos de idade, a extensão da madeira juvenil vai até 52% do seu raio.
Demarcation of juvenile and mature wood of Corymbia citriodora
Keywords: Length of fibers; Wood anatomy; Comprimento de fibras; Anatomia da madeira; Corymbia citriodora